The role of recreational sports activity in achieving psychosocial adjustment for the mentally retarded within pedagogical medical centers. - rahli, Mourad (sports creativity, 2025)
There are categories of individuals in society whose upbringing and personality development are difficult to achieve through ordinary material, human, and moral means, as they suffer from maladjustment, whether physical, mental, psychological, or social. This is due to deficiencies or impairments in the development of one or more bodily functions or senses, which—according to structural-functional personality analysis—creates psychological and social problems that prevent them from fully benefiting from experiences available to the average person, and hinder their ability to compete on an equal footing with other members of society. These groups are scientifically termed "people with disabilities." Undoubtedly, enabling individuals with intellectual disabilities to achieve psychological well-being requires the development of specialized programs and activities. Algeria has given this matter considerable attention, establishing medical-pedagogical centers with their own specific objectives and programs, including medical, academic, psychological, physical, and recreational activities.